Sosialisasi New Normal Pada Transportasi Massal di Kota Semarang: Socialization of New Normal on Mass Trasnportation in Semarang City - Amrita Winaya; Tigo Mindiastiwi; Purwantini (Jurnal Suara Pengabdian 45, 2022)
The Covid-19 pandemic that has been going on since the end of 2019 has had a broad impact on various sectors, one of which is in the transportation sector. If this transportation is carried out using mass transportation or public transportation, then during the Covid-19 pandemic it will make it easier for the virus to spread if these public transport users do not comply with health protocols. Socialization regarding the use of mass transportation in the new normal era has been carried out in various locations and levels of society. In general, people still do not understand about this new normal era, so many do not comply with health protocols. This social service activity aims to provide insight to the community, especially groups of young high school students in using mass transportation in the new normal era. It is hoped that the teenagers can increase their awaraness of implementing health protocols so that they can reduce the spread of the virus that causes the Covid-19 pandemic.